Body temperature and mouse scoring systems as surrogate markers of death in cecal ligation and puncture sepsis - Safiah H. C. Mai (Intensive Care Medicine Experimental, 2018)
Abstract Background Despite increasing ethical standards for conducting animal research, death is still often used as an endpoint in mouse sepsis studies. Recently, the Murine Sepsis Score (MSS), Mouse Clinical Assessment Score for Sepsis (M-CASS), and Mouse Grimace Scale (MGS) were developed as surrogate endpoint scoring systems for assessing pain and disease severity in mice. The objective of our study was to compare the effectiveness of these scoring systems and monitoring of body temperature for predicting disease progression and death in the cecal ligation and puncture (CLP) sepsis model, in order to better inform selection of surrogate endpoints for death in experimental sepsis. Methods C57Bl/6J mice were subjected to control sham surgery, or moderate or severe CLP sepsis. All mice were monitored every 4 h for surrogate markers of death using modified versions of the MSS, M-CASS, and MGS scoring systems until 24 h post-operatively, or until endpoint (inability to ambulate) and consequent euthanasia. Results Thirty percent of mice subjected to moderate severity CLP reached endpoint by 24 h post-CLP, whereas 100% undergoing severe CLP reached endpoint within 20 h. Modified MSS, M-CASS, and MGS scores all increased, while body temperature decreased, in a time-dependent and sepsis severity-dependent manner, although modified M-CASS scores showed substantial variability. Receiver operating characteristic curves demonstrate that the last recorded body temperature (AUC = 0.88; 95% CI 0.77–0.99), change in body temperature (AUC = 0.89; 95% CI 0.78–0.99), modified M-CASS (AUC = 0.93; 95% CI 0.85–1.00), and modified MSS (AUC = 0.95; 95% CI 0.88–1.01) scores are all robust for predicting death in CLP sepsis, whereas modified MGS (AUC = 0.78; 95% CI 0.63–0.92) is less robust. Conclusions The modified MSS and body temperature are effective markers for assessing disease severity and predicting death in the CLP model, and should thus be considered as valid surrogate markers to replace death as an endpoint in mouse CLP sepsis studies.